Effect of Cadmium Contaminants against Absorption of Cadmium and The Results of 3 Types of Families Brassicaceae Vegetables On Peat Soil - Panthera Boy, Godefridus Delanova; Suswati, Denah; Susana, Rini (Jurnal Sains Mahasiswa Pertanian, 2014)
Cadmium (Cd) is a heavy metal that is often the pollutants on agricultural land. This research aimed to study the absorption of cadmium (Cd) and yield of the three kinds family brassicaceae grown in peat media contaminated with cadmium (Cd). The method used in this research was Split Plot Design. As the main plot are 3 types of vegetables consist of 3 types of mustards: mustard greens, Chinese cabbage, and Chinese broccoli. Sub plot the dose cadmium treatment consisting of c0 (no contaminant), c1 (Soil contaminated with 2 mg Cd/kg soil), c2 (Soil contaminated with 4 mg Cd/kg soil), c3 (Soil contaminated with 8 mg Cd/kg soil), c4 (Soil contaminated with 16 mg Cd/kg soil) and c5 (Soil contaminated with 32 mg Cd/kg soil). The observation variables in this study consisted of soil pH, available Cd after incubation (mg/kg), the shoot fresh Weight (g), and Total Cd absorption of shoot (mg). The results showed that soil reaction (pH) after contaminant application has not changed significantly, whereas availability of cadmium increase of dose of Cd contaminant. Dose of Cd contaminant influenced the fresh weight of three crops used. Cd contaminant at the highest dose (32mg Cd/kg) tend to decrease fresh weight of mustard green and chinese cabbage but not to chinese broccoli. Dose of Cd contaminated significantly effected the absorption of Cd in plant, the higher the dose the greater the absorption of Cd by plant. Keywords: Cadmium (Cd), Brassicaceae, Peat Soil